Autogenic Relaxation on Cardiac Pain in Patients with Acute Coronary Syndrome (Palliative Review Study of Patients with Acute Coronary Syndrome after a Heart Attack at Margono Sokarjo Hospital, Purwokerto) - Supadi Supadi; Widjijati Widjijati; Welas Haryati (Budapest International Research and Critics University, 2021)
Every year more than 36 million people die from non-communicable diseases (NCD), which is about 63% of deaths caused by NCDs. Globally, NCD which is the number one cause of death each year is cardiovascular disease that can occur before the age of 60 years, and 90% of these premature deaths occur in low and middle income countries. Central Java Province data based on reports from hospitals, the highest cases of coronary heart disease were in the city of Semarang, amounting to 4,784 cases (26.00%) compared to the total number of cases of coronary heart disease in other districts/cities in Central Java. When viewed based on the total number of other NCD cases in Klaten Regency, it was 3.82%. Meanwhile, the second highest case was in Banyumas Regency, which was 2,004 cases (10.89%) and when compared to the total number of other NCDs in Banyumas Regency, it was 9.87%. The fewest cases were found in Tegal Regency, namely 2 cases (0.01%) (Health Profile of Central Java Province, 2014). Pain managementis part of the discipline of medical science related to efforts to relieve pain or pain relief. Autogenic relaxation technique, which is a non-pharmacological therapy, will increase the supply of oxygen to the tissues, thereby reducing the level of pain experienced by individuals. This research is a quantitative quasi-experimental without control group Pre post test design. This study used a cross-sectional observational analytic design, namely to analyze the effect of autogenic relaxation on the degree of chest pain of clients with Acute Coronary Syndrome (ACS) after an acute heart attack at the hospital. The sample obtained 18 respondents with details of 14 male and 4 female. The sampling technique in this study was purposive sampling. Characteristics of respondents in this study the majority of men (77.8%). Based on the age characteristics, it was found that the age range of the respondents was 51-69 years with a mean of 59.8 years. The results of the study showed that autogenic relaxation had a significant effect on reducing the chest pain scale in respondents after ACS (p = 0.000)